Distance Education at University of Cape Coast: Enrolment decisions, expectations and challenges of students - Tweneboah-Kodua, Kennedy (University of Cape Coast, 2020)
The study explored the enrolment decisions, expectations and challenges of Distance Education students in the University of Cape Coast (UCC). The study employed descriptive survey research design. The population for the study was the post-diploma degree in education students of the college. The study was targeted at all final year students of the post-diploma in education programme. Cluster and stratified sampling procedure were employed to select 176 students to participate in the study. The study used a questionnaire as the main instrument for data gathering. Descriptive statistics (frequencies and percentages) was computed for the descriptive data. The study revealed that students of the College of Distance Education (CoDE), University of Cape Coast (UCC), were furthering their education to gain competence and skills. It was evident that the students expected the utilisation of modules or course books as the instructional medium for the distance education. It was revealed that the students had the expectation of becoming professional and skilful teachers in their field of study. The study found that the greatest challenge of students is limited time to study on their own. It is recommended that the management of College of Distance Education, University of Cape Coast, together with the Distance Education Students Association (DESAG) should organise seminars for students on time management especially where their learning is coupled with work.
x, 82p:, ill.
Keywords: Distance Education; Enrolment Decisions; Expectations